Determinants of retirement saving behaviour among staff in Yayasan Melaka / Khairunnisa Abu Kasim and Nurul Syazwana Hamzah - Abu Kasim, Khairunnisa; Hamzah, Nurul Syazwana (Faculty of Business and Management, 2013)
This research conducted focusing on the factors that influence retirement savings behavior among staff in Yayasan Melaka. Retirement saving behavior is very important to ensure that all working Malaysian citizens have knowledge about retirement scheme. In Malaysia, there still many people not aware towards saving for their retirement. In support of the government endeavor, many initiatives had been developed to help the public to create savings for their retirement. For example, the 1Malaysia Retirement Savings Scheme had been launched by our Prime Minister, Datuk Seri Najib Tun Razak in Budget 2010, introduced as government initiative to ensure that the self-employed and have no regular income during their retirement savings. This scheme was effective from January 3, 2010. In line with this, the main objectives of this study are (1) To examine the relationship between goal clarity, social interaction, self-control that contribute toward retirement saving behavior among staffs in Yayasan Melaka and (2) to identify the most influence factors that affect retirement saving behavior among staffs in Yayasan Melaka. The respondents of this study were the staffs in Yayasan Melaka that located in Melaka area. 110 questionnaires had been distributed among them. The researcher had used cluster sampling as a sampling technique. The process of analyzing and interpreting data is collected. The researcher also has come out with a few recommendations to be taken into consideration. By implementing these recommendations, it will help the public realize the importance to saving for their retirement.